Польский переселенческий говор в Респ ублике Хакасия и в Красноярском Крае РФ - Егоров, Илья Михайлович (Slavia Occidentalis, 2016)
The article deals with the essential aspects of the phonetic and, primarily, grammatical system of the Polish immigrant dialect spoken in two villages in Western Siberia: Znamenka (Bogradsky District of the Republic of Khakassia) and Alexandrovka (Krasnoturansky District of Krasnoyarsk Krai). The dialect appeared in the Yeniseysk Governorate of the Russian Empire at the end of 1890s as a result of Polish rural migration from Volhynia to Siberia. Before that, the ancestors of those settlers had moved to Volhynia from Masuria. The examined dialect shows relatively good preservation of its original system. At the same time, it has been strongly influenced by Russian, as the dominant language of its surroundings. The main effect of this intensive contact is the further development of trends that had taken place in the original dialect system, which have been supported by the Russian language.